EMPOWERMENT OF RURAL WOMEN FARMERS AND FOOD PRODUCTION IN IMBULPE DS DIVISION IN SRI LANKA: A HOUSEHOLD LEVEL ANALYSIS - Dilini Rathnachandra; P Malkanthi (Agricultural Socio-Economics Journal, 2022)
Women empowerment and gender equity are two significant aspects of the sustainable development of a country. As Sri Lanka is on the way towards sustainable development, this study was conducted to identify the current situation of women farmers’ empowerment and food production in Imbulpe (Divisional Secretariat) DS division of the country. A sample of 300 women farmers was randomly selected for the study, from seven selected Grama Niladhari divisions (GN) of Imbulpe DS division. A field survey was carried out to data collection through a pre-tested, self-administered questionnaire from April to July 2019. Descriptive statistics, correlation analysis and regression analysis were used as the data analysis methods. Results convey that most of the women farmers were middle aged, married and had two children within their family. Furthermore, most of the respondents had secondary level of education and their average family size was four, 1.25 acres was the average farm land size. They had about 16 years of experience in the field of agriculture sector. The average monthly income of the respondents was 25,000.00 LKR (Sri Lankan Rupees). Women empowerment was measured by using the models of Rahman and Naoroze (2007); Praveen and Leonhauser (2004) with necessary modifications according to the study area. Most of the women farmers were showed social empowerment aspect and political empowerment aspect reported as the least empowerment aspect according to the unit empowerment measures. Out of the socio-economic factors size of the farm land, number of agricultural training programs participated, monthly income of the family, respondents level of education and number of agricultural training programs attended were indicated significant and positive effect for the empowerment of women farmers. Accessibility of credit facilities and agricultural extension program participation showed that there was a considerable impact on food production rather than the cultivable land size and utilization of modern farming technologies for food production. Therefore, providing of timely important agricultural education and training programs, enhance awareness level of modern farming technology utilization, better micro finance programs and agricultural credit facilities will be able to upgrade the level of empowerment of women farmers in Imbulpe DS division furthermore.